STUDENTS’ ATTITUDES TOWARD BLENDED LEARNING THROUGH GOOGLE CLASSROOM IN GENERAL ENGLISH COURSE - Irfan Fajrul Falah; Chairuddin Chairuddin (Universitas Samudra, 2022)
During the pandemic of Covid-19, offline and online learning are recommended by the government of Indonesia. It is believed by using both offline and online, students will have their opportunity in enhancing their self regulated learning, which seems very effective in this hard time. Therefore, this study will investigate the students’ attitudes on the implementation of blended learning especially in general English course. This study employed survey method in gaining the data where around 92 students of Primary School Education Study Program were involved both in filling questionaire. Interview was also conducted by the researchers to validate and elicite more feedback on this study. The finding shows that almost 76.3% of the students were positive and satisfied on the implementation of blended learning. By applying blended learning, students were also permited to repeat or re-open the lesson without any pressure. By conducting this study, several shortages were also appeared where internet connection was the main problem. Theacher’s lack of online learning design was also a thing to take into consideration. Blended learning has been very effective. Hence, this study support the refinement of the implementation especially in the area where internet connection is a thing to be concerned.